2021
DOI: 10.21608/ejchem.2021.100722.4678
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and investigation of green hydrogels for simultaneous removal of mercuric cations and methylene blue from aqueous solutions

Abstract: A green composite comprised of guar gum enforced with different weight ratios (1, 2, and 3%) of talc powder (TP) as inorganic support. This group of green sorbent materials was introduced to remove methylene blue and toxic chemical modification was proved by the IR spectroscopy and the prepared hydrogels were investigated by X (XRD) for their crystallinity. The thermal properties of the green sorbents wer (TGA). Scanning electron microscopy (SEM) and Atomic force microscopy (AFM) were used to investigate the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Then, according to the height measurement, it can be expected that (Ch-Er) 3 would give maximum removal; the elimination experiments proved this prediction. These findings agree with our previous work (Keshawy et al 2022).…”
Section: Afm Study Of Chitosan-erythritol Hydrogelssupporting
confidence: 94%
“…Then, according to the height measurement, it can be expected that (Ch-Er) 3 would give maximum removal; the elimination experiments proved this prediction. These findings agree with our previous work (Keshawy et al 2022).…”
Section: Afm Study Of Chitosan-erythritol Hydrogelssupporting
confidence: 94%
“…The intensity of this layer increased with increasing removal capacity. In our previous works, 34,35 we could apply the AFM for confirming the adsorption process by comparing the AFM outcomes before and after metal uptake. We found that the adsorbed species appear as a bright layer covering the surface causing the increase in the height measurement and the change in roughness values.…”
Section: Adsorption Kinetics 381 Adsorption Kinetics Of the Chitosan-...mentioning
confidence: 99%
“…AFM is a modest tool for topography charcaterization of different material. It is used in describing the surface of hydrogels in previous works [10,32]. In this work, the AFM is used to study the surface topography, the porous structure, and the height of GG-PC/PAAm/ZnO 0 , GG-PC/PAAm/ ZnO 3 , and GG-PC/PAAm/ZnO 7 (Fig.…”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 99%